Comparison of ascorbic acid and lignin accumulation in four white celery varieties and transcriptional profiling of genes related to the metabolic pathways. Issue 1 (1st January 2020) - Yin, Lian; Xing, Guo-Ming; Sun, Sheng; Wang, Guang-Long; Liu, Jie-Xia; Ding, Xu; Shen, Di; Feng, Kai; Xu, Zhi-Sheng; Xiong, Ai-Sheng
Abstract: White celery ( Apium graveolens L.), a variety of common celery, is an important leafy vegetable in the Apiaceae family and is famous for its nutritional value. However, limited work has been devoted to quality formation and regulation in white celery. In this study, four white celery varieties, 'Xuebaiqincai', 'Saixue', 'Baiganshiqin' and 'Ruixue', were selected and analyzed for the comparison of ascorbic acid (AsA) and lignin levels, which are two important quality evaluation indicators in celery. The expression levels of the genes involved in AsA and lignin metabolic pathways were also detected. In the leaf blades, the AsA content was highest in 'Xuebaiqincai' compared with other varieties, whereas the most abundant AsA levels in the petioles were observed in 'Baiganshiqin' and 'Ruixue'. The expression levels of AsA-related genes varied among the studied varieties. The highest level was detected in 'Xuebaiqincai', whereas other varieties exhibited relatively lower levels. The lignin content in the leaf blades was lower than that in the petioles. Correspondingly, the transcript profiles of genes involved in lignin biosynthesis were in accordance with the different levels in the petioles and blades. The results of this study provide potentially useful information for white celery breeding aimed at quality improvement and regulation.